Prevalence of Alzheimer's Disease and Parkinson's Disease in China: An Updated Systematical Analysis - Cui, Lei; Hou, Na-Na; Wu, Hong-Mei; Zuo, Xiang; Lian, Yi-Zhi; Zhang, Chao-Nan; Wang, Zhen-Feng; Zhang, Xiong; Zhu, Jian-Hong (Frontiers in Aging Neuroscience, 2020)
Background: Alzheimer’s disease (AD) and Parkinson’s disease (PD) are two major neurodegenerative diseases worldwide. Demographic ageing is in rapid progress in China. Up-to-date estimates of AD and PD prevalence have not been provided. Methods: Studies that reported the prevalence of AD and PD in China were identified via a systematic database search from 1985 to 2018. Meta-analysis, local polynomial regression and autoregressive integrated moving average model were used for analyses. Results: A total of 99 studies were included in the study with population at 385312 and 227228, respectively for AD and PD. The overall prevalence of AD and PD following age standardization was 3.20% [95% confidence interval (CI) = 3.17-3.23] and 1.06% (95% CI = 1.02-1.10), respectively in individuals over 60 years old. The rates increased drastically for every 10-year increment of age. The yearly prevalence of AD was predicted to increase from 3.81% to 6.17% in the next five years. Significant differences were observed between genders [male to female odds ratio (OR) for AD = 0.57, 95% CI = 0.51-0.64; OR for PD = 1.25, 95% CI = 1.06-1.46], and between education levels (Illiterate to non-illiterate OR for AD = 2.99, 95% CI = 2.38-3.75), but not between urban and rural settings. Conclusion: Our results provide an updated insight into the epidemiology of AD and PD in China and their associated rates and ratios. The findings may facilitate China policy makers and health professionals mitigate the related health issues.